2017
DOI: 10.7575/aiac.ijalel.v.7n.1p.152
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Genre of Academic Oral Presentations: A Critical Review

Abstract: Conducting Academic Oral Presentation (AOP) is an endeavour for undergraduates although it is a key academic genre for undergraduates. Despite its importance, there remains a paucity of studies on this oral genre in the Malaysian context as shown in the body of the literature. This paper provides a critical review of the literature on AOP and discusses the advantages and limitations of the previous studies to date on this oral genre. The literature shows most studies that adopt the genre analysis approach typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…For example, their previous educational experiences do not foster oral presentations skills, with little or no affordances to ask questions in the classroom (Hristova, 2014). Moreover, prospective teachers feel anxiety to present and share their point of view in front of an audience (Beatty & Friedland, 1990;Kaur & Ali, 2018).While professional presentations require a command on language, clarity of concepts, and self-confidence (Lucas,2011); it is observed that prospective teachers coming from an English as Foreign Language (EFL) background often lose their confidence because of the difficulties to communicate in a foreign language (Miles, 2009;Yan & Horwitz, 2008),and feel anxiety to speak in front of their peers (McCroskey & Richmond, 1992). Similarly, in the context of present study, EFL background presents a considerable challenge to prospective teachers since their prior educational experiences were predominantly influenced by the native and local languages (Apple, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, their previous educational experiences do not foster oral presentations skills, with little or no affordances to ask questions in the classroom (Hristova, 2014). Moreover, prospective teachers feel anxiety to present and share their point of view in front of an audience (Beatty & Friedland, 1990;Kaur & Ali, 2018).While professional presentations require a command on language, clarity of concepts, and self-confidence (Lucas,2011); it is observed that prospective teachers coming from an English as Foreign Language (EFL) background often lose their confidence because of the difficulties to communicate in a foreign language (Miles, 2009;Yan & Horwitz, 2008),and feel anxiety to speak in front of their peers (McCroskey & Richmond, 1992). Similarly, in the context of present study, EFL background presents a considerable challenge to prospective teachers since their prior educational experiences were predominantly influenced by the native and local languages (Apple, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Presentations showcase current or emerging projects, practice challenges or finalised research. 38 They can be used to encourage collaboration between research teams, or to define research territory.…”
Section: Academic Presentationmentioning
confidence: 99%
“…They argue that the transferability of templates might actually be counterproductive and instead advocate creating more genre awareness among learners. Kaur and Ali (2018) note that most previous research has focused only on parts of oral presentations, often neglecting the rhetorical structure as a totality, particularly the multimodal features that bind speech, written text, visuals, and the moves made between these. While noting that the form of an academic presentation is linear, it is not rigid-as there appear to be a variety of optional moves available to the speaker.…”
Section: Pedagogical and Classroom Considerations For The Esp/eap Instructormentioning
confidence: 99%